The analysis of routinely performed his top a tho logical examination in tonsillectomies indicated by chronic tonsillitis - Irfan, Mohamad (2008)
The Analysis Of Routinely Performed Histopathological Examination In Tonsillectomies Indicated By Chronic Tonsillitis The objective of this study was to see the outcome of sending routine specimen for histopathological examination in term of final diagnosis and incidental findings. This was an observational prospective study whereby 197 patients who had undergone tonsillectomy between August 2005 to January 2007 were recruited. Malignant suspicion cases were excluded. All of the operations were performed with conventional dissection method at Hospital Universiti Sains Malaysia. All specimens were sent for histopathological examination as routinely performed. All of the studied specimens showed reactive lymphoid hyperplasia changes. No specimen noted to be malignant. Actinomyces colonies were common incidental findings. CONCLUSION : This study concluded that the clinical diagnosis was no different with the histopathological result. The examination should not be performed as a routine procedure unless if there was any malignant suspicion or for medicolegal purposes.